Influence of obesity on subgingival microbiota composition in subjects with different periodontal status: a systematic review - Alarcón-Sánchez, Mario Alberto (2024)
Objective: This systematic review aimed to investigate the changes in the composition of the subgingival microbiota among subjects with normo-weight, overweight and obesity, in conditions of periodontal health and disease. Materials and Methods: The protocol for this study was designed following PRISMA guidelines. Records were identified using different search engines (PubMed/MedLine, Scopus and Web of Science). Observational studies, in human subjects diagnosed with obesity (BMI >30kg/m2) and periodontal disease (gingivitis and periodontitis), on the analysis of subgingival microbiota were selected. Eight articles were included. Results: The subgingival microbiota of 1,229 subjects (n=894 exposure group and n=335 control group) was analyzed. Periodontal pathogens were the most common bacteria detected in subjects with obesity and periodontitis (Porphyromonas gingivalis, Tannerella forsythia, Campylobacter gracilis, Eubacterium nodatum, Fusobacterium nucleatum spp. vincentii, Parvimonas micra, Prevotella intermedia, Campylobacter rectus, and Aggregatibacter actinomycetemcomitans), as along with some accessory pathogens such as: Streptococcus gordonii, and Veillonella parvula that favor the virulence of late colonizers. Conclusions: Although there are evident alterations in the composition of the subgingival microbiota in subjects with obesity and periodontitis, it is still a challenge to identify a specific pattern of microbiota in these subjects. If associations between subgingival plaque microorganisms and obesity are confirmed, microbiome analysis could be a useful tool to improve preventive measures and the management of people with obesity.